2021
DOI: 10.1186/s13756-021-01021-7
|View full text |Cite
|
Sign up to set email alerts
|

Staphylococcus aureus - selective reporting of antibiogram results and its impact on antibiotic use: Interventional study with a reference group on the effect of switching from non-selective to selective antibiotic reporting

Abstract: Background Antimicrobial stewardship (AMS) strategies worldwide focus on optimising the use of antibiotics. Selective susceptibility reporting is recommended as an effective AMS tool although there is a lack of representative studies investigating the impact of selective susceptibility reporting on antibiotic use. The aim of this study was to investigate the impact of selective susceptibility reporting of Staphylococcus aureus (S. aureus) on antibiotic consumption. Enhancing the use of narrow-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 39 publications
0
0
0
Order By: Relevance
“…In this study, these two points were not present and selective reporting of antibiotic susceptibility test results led to a significantly higher use of ampicillin. Likewise, Lestin-Bernstein et al [ 9 ] reported a significantly higher use of narrow-spectrum penicillin after the implementation of selective reporting in BSI with Staphylococcus aureus . In this study, a comment on the microbiological report was also included, directing clinicians to the preferred choice of therapy; this possibly might have also contributed to the success of the intervention.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, these two points were not present and selective reporting of antibiotic susceptibility test results led to a significantly higher use of ampicillin. Likewise, Lestin-Bernstein et al [ 9 ] reported a significantly higher use of narrow-spectrum penicillin after the implementation of selective reporting in BSI with Staphylococcus aureus . In this study, a comment on the microbiological report was also included, directing clinicians to the preferred choice of therapy; this possibly might have also contributed to the success of the intervention.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical microbiology therefore is an essential part of antibiotic stewardship. Selective reporting of antibiotic susceptibility test results might facilitate pathogen-directed antibiotic therapy and thus be an important antibiotic stewardship intervention [7][8][9], which was also highlighted in the previously revised German guideline on the rational use of antibiotics in medicine [10]. The aim of this study was to analyse whether selective antibiotic susceptibility reporting resulted in more focused antibiotic therapy in patients with Streptococcus pneumoniae bloodstream infection (BSI).…”
Section: Introductionmentioning
confidence: 99%